Twin deficits hypothesis and Feldstein-Horioka puzzle in Asian countries: is Keynesian alive? - Baharumshah, Ahmad Zubaidi; Soon, Siew Voon; Ismail, Hamizun (Faculty of Economics and Management, Universiti Putra Malaysia, 2012)
The relevance of the twin deficits hypothesis in 13 Asian countries is examined, taking into account the presence of a structural break. The major findings based on an extended data set are: 1) the budget balance plays a significant role in the determination of a current account balance, and there is strong evidence supporting the Keynesian view of the twin deficits; 2) investment and real exchange rate have a noticeable impact on current account balance; and 3) the Feldstein-Horioka puzzle seems to be valid in most countries.